2021
DOI: 10.1172/jci.insight.146852
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3/caspase-1/GSDMD–mediated pyroptosis exerts a crucial role in astrocyte pathological injury in mouse model of depression

Abstract: Emerging evidence suggests that astrocyte loss is one of the most important pathological features in the hippocampus of patients with major depressive disorder (MDD) and depressive mice. Pyroptosis is a recently discovered form of programmed cell death depending on Caspase–gasdermin D (Casp-GSDMD), which is involved in multiple neuropsychiatric diseases. However, the involvement of pyroptosis in the onset of MDD and glial pathological injury remains obscure. Here, we observed that depressive mice showed astroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(71 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…A hypothesis was arisen that NLRP3 inflammasome may closely link with pyroptosis. In fact, a plenty of research results confirm the hypothesis in term of coexistence between activation of NLRP3 inflammasome and occurrence of pyroptosis in organism [ 103 ][ 104 ][ 105 ][ 106 ][ 107 ][ 108 ][ 109 ]. Many in-depth studies have found the molecular mechanism of NLRP3 inflammasome in relation to pyroptosis.…”
Section: Relation Between Nlrp3 Inflammasome and Pyroptosismentioning
confidence: 71%
See 1 more Smart Citation
“…A hypothesis was arisen that NLRP3 inflammasome may closely link with pyroptosis. In fact, a plenty of research results confirm the hypothesis in term of coexistence between activation of NLRP3 inflammasome and occurrence of pyroptosis in organism [ 103 ][ 104 ][ 105 ][ 106 ][ 107 ][ 108 ][ 109 ]. Many in-depth studies have found the molecular mechanism of NLRP3 inflammasome in relation to pyroptosis.…”
Section: Relation Between Nlrp3 Inflammasome and Pyroptosismentioning
confidence: 71%
“…Specifically, NLRP3 inflammasome assembly promote pro-caspase-1 activation into active caspase-1, which accelerate pro-inflammatory factor release and GSDMD pore formation in cell membrane, and further induce pyroptosis [ 103 ]. NLRP3 inhibitors can alleviate or reverse the activation of NLRP3 inflammasome-mediated pyroptosis [ 104 ][ 105 ][ 106 ][ 107 ][ 108 ][ 109 ]. Blocking NLRP3 and pyroptosis is a new and effective strategy to inhibit inflammation and its related diseases, which may provide a unique perspective to deeply understand the relationship between NLRP3 inflammasome and pyroptosis [ 110 ].…”
Section: Relation Between Nlrp3 Inflammasome and Pyroptosismentioning
confidence: 99%
“…Pyroptosis is a unique type of programed cell death depending on inflammatory caspase–mediated activation of GSDMD ( Li et al, 2021 ). Activated GSDMD protein formed the pore in the cell membrane, causing cellular swell and rupture and the release of proinflammatory IL-1β and IL-18 ( Ding et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that caspase-1 activation is initiated by the assembly of the NLRP3 inflammasome, comprised of NLRP3, ASC, and caspase-1, and activated caspase-1 promoted the secretion of mature IL-1β and IL-18 to amplify the inflammatory response ( Li et al, 2021 ; Sun et al, 2022 ). We previously reported the increase of NLRP3 signaling in TCE-induced kidney damage ( Xie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depressive mice were shown to present astrocytic loss that was promoted by pyroptotic cellular death. The pyroptotic process was triggered by the activation of the NLRP3/caspase-1/GSDMD pathway ( Li et al, 2021 ). Also, in mice with depression induced by chronic mild stress, it was reported that kynurenine, a tryptophan metabolite, acted as a pro-inflammatory factor in astrocytes.…”
Section: Inflammasomes and Astrocytesmentioning
confidence: 99%